Non-vitamin K antagonist oral anticoagulants in atrial fibrillation patients with chronic kidney disease: A systematic review and network meta-analysis. (15th March 2017) - Andò, Giuseppe; Capranzano, Piera
Abstract: Background: Currently there is lack of head-to-head comparisons between different Non-Vitamin K Antagonist Oral Anticoagulants (NOACs), especially in more risky subgroups, as those with chronic kidney disease (CKD). Methods: We assessed the relative efficacy and safety of the four NOACs on the market in a systematic review and network meta-analysis of patients with atrial fibrillation (AF) and moderate CKD enrolled in the phase 3 randomized trials. A Bayesian framework was used to perform the network meta-analysis. Treatment hierarchy was assessed by surface under the cumulative ranking (SUCRA) curves. Results: Five randomized trials including 13, 878 AF patients with moderate CKD were identified. Full/Single dose NOACs were associated with significant reductions in the odds of stroke/systemic embolism (odd ratio [OR] 0.79, 95% credible intervals [CrI] 0.67–0.94) and major bleeding (OR 0.74, 95% CrI 0.65–0.86) compared with Warfarin. Dabigatran 150 had the highest probability of being ranked first with respect to efficacy (SUCRA 0.96), whereas Apixaban had the second highest (SUCRA 0.67); Dabigatran 110, Rivaroxaban and Edoxaban High-Dose showed similar probabilities of being ranked first for efficacy (SUCRA 0.54, 0.53, 0.51, respectively); with respect to safety, only Apixaban and Edoxaban High Dose had a probability > 50% of being ranked first (SUCRA 0.84 and 0.61, respectively). Conclusions: Indirect comparisons generated the hypothesis that Apixaban and Edoxaban High-Dose might be more likely associated with a better net clinical profile in AF patients with moderate CKD. These findings may potentially guide physicians in selecting the most appropriate NOAC for each patient, while waiting for dedicated evidences.